Digital skills of university teachers: A literature review - Paco Matamoros, Lucy (2024)
Objective: Analyze the state of the art of digital competencies of university teachers Method: a bibliographic review of scientific articles on digital skills in university teachers, published during the years 2018 and 2022, was carried out, taking into account the methodological protocols suggested for the bibliographic review. The search strategy incorporated the use of databases: LILACS, ERIC, Scopus, PubMed, Web of Scencie. and Boolean operators for combining the descriptors. 179 articles were identified and reviewed, of which 20 articles were useful. The results: digital skills vary depending on the age group and academic grade, and indicate that the training improves their skills and use of these tools during teaching-learning. Conclusion: most studies report that teachers have a basic to medium level of digital competencies, these are complex processes that teachers must take on the challenge of working with the resources of the digital era and allowing them to interact and use new strategies in the training of the new generation of nurses.